A proposal for intergenerational mentoring in the training of school headteachers (Revista Lusófona de Educação, 2026)
In Portugal, in recent months, dozens of school principals have left office after reaching the legal limit for candidacies. Some of these headteachers have held these leadership positions for around two decades and, during that time, have shaped the school groups they have coordinated, the leadership profiles they have naturalised in their schools, and the local policies they have helped to design to respond locally to the educational problems they have faced. How can the education system capitalise on this experience? Based on the confluence of three key concepts: intergenerationality, mentoring, and professional development, this article aims to discuss how these three concepts can be articulated in the context of educational leadership. This is an exploratory study that uses in-depth interviews with four headteachers at the end of their term. As a result of this work, it was possible to inventory the possibilities and constraints of a training proposal on mentoring for school headteachers to be offered to former professionals who are now ending their long terms of office, so that, as a result of this training, they can ensure the sustainability, innovation, and resilience of school leadership through the systematic transfer of knowledge, the promotion of mutual respect, and the development of future school leaders.Keywords: Intergenerational learning; Mentoring; School leadership